IMPLEMENTASI KEBIJAKAN PENDIDIKAN - Cucu Atikah; Hany Tutut Handayani; Mariyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Implementation of Education Policy is an important step in achieving educational targets set by the government or agency concerned. The aim of implementing the Education Policy is to make the policy a reality in accordance with the plans that have been prepared. This research uses a qualitative approach by conducting a review of various literature and references related to the implementation of Education Policy. The information used comes from books and journal articles that are relevant to this topic. The implementation process involves a series of steps, starting from policy formulation, establishing implementation guidelines, to implementation in the field. With a deep understanding of the process of implementing education policies, it is hoped that it can produce an education system that is more effective, efficient and inclusive for all levels of society.